Surgical Resection of Left Atraial Myxoma in A Male Child - A Case Report - Tarik, Khalifa Mahmud; Hossain, Makbul; Ahmed, Syed Shafi (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2015; VOL 39 (3) :154-156